A New Method for Predicting Residual Strength of Rock in Water Diversion Tunnel Using Drilling Process Monitoring - Wanfei Gao (Shock and Vibration)
The peak and residual strengths of rock materials are important parameters for the stability evaluation of rock engineering, especially water diversion tunnels. A friction-strengthening model based on Hoek–Brown model is proposed to determine peak and residual strength of rock. The proposed model parameter, contact friction coefficient of rock, controls the nonlinearity of the peak strength and residual strength. With a great amount of data from publications examined, the relationship between the friction coefficient and the parameters in the Hoek–Brown model is studied. A new field method using drilling process monitoring was proposed to predict the peak strength and residual strength. The results show that the predicted strength for four types of rock is in good agreement with those of the standard tests in laboratory. Their errors are within the error range of 15% compared to the results from the tested results in laboratory. Although the proposed model is empirical, the parameters in the proposed model have clear physical meaning, and it can successfully predict the peak strength and residual strength of hard rock, medium rock, and weak rock using drilling process monitoring in the field. This practical method should have a great potential for field application in rock engineering.